The neighborhood has its own rules: latinos and african americans in South Los Angeles - Martinez, Cid Gregory (New York University Press, 2016)
Introduction: managed violence -- Neighborhood councils: City Hall competes with the street for legitimacy -- Alternative governance: Latino and African American interrelations outside of City Hall -- Neighborhood institutions: safety from violence, and the Catholic Church -- Faith is the opposite of fear: the Catholic Church as alternative governance -- Street justice: gangs, the informal economy, and neighborhood residents -- Responding to violence, keeping the peace: interracial relations between black and Latino youth gangs (co-authored with Dominic Rivera) -- Conclusion: revisiting alternative governance